Evaluation of the effect of high pressure in quality of edible flowers: Viola × wittrockiana - Fernandes, Luana (2018)
Edible flowers are becoming more popular, but they are quite perishable, with a very short shelf life. So, the industry is interested in improving their marketability, not only as fresh but also as processed products. High Pressure Processing (HPP) is an innovative, emerging technology already in use by the industry. In order to determine the potential of this new food technology to maintain the appearance of white pansies (Viola x wittrockiana), in the presente study some combinations of high pressure (75, 150, 450 MPa) and holding time (5 and 10 min) were performed. The pansies treated with 75/5 and 75/10 MPa/min showed a similar appearance to fresh flowers, while pansies treated with 150/10, 450/5, 450/10 MPa/min had changes on the appearance, having the violet color expanded to the white part. All combinations of pressure/time treatments kept the water activity at high values. Furthermore, some changes were observed on the weight loss and color, which were more pronounced at 150 and 450 MPa. So, HPP of pansies applied for small holding times (5 or 10 mins) and at a pressure of 75 MPa is a possible methodology, without causing changes in pansies' appearance.